Perspektif Kebijakan Kontra-Terorisme ASEAN dan Perbedaan Paradigma Penanggulangan Terorisme oleh Negara-Negara Anggota ASEAN - Hadi Pradnyana (Politicos: Jurnal Politik Dan Pemerintahan, 2022)
This research examines the perspective of ASEAN's counter-terrorism policy and ASEAN member states. Observing ASEAN's counter-terrorism policy instruments and the approach of ASEAN member states to these instruments. Based on the massive threats of terrorism that have occurred in Southeast Asia, especially since the 9/11 incident in 2001. Qualitative descriptive is used as a research method, using a literature study approach. The results showed that ASEAN adopted a law enforcement approach in countering terrorism. ASEAN for the first time issued a counter-terrorism policy instrument specifically through the ASEAN Declaration on Joint Action to Counter Terrorism 2001, after 9/11. Then followed by other instruments such as the ASEAN-US Joint Declaration for Cooperation to Combat International Terrorism 2002, Joint Declaration on Cooperation to Combat Terrorism 2003, ASEAN Convention on Counter Terrorism (ACCT) 2007, and joint declarations with external dialogue partner countries such as United States, European Union, India, Australia, Russia, Japan, South Korea, New Zealand, Pakistan and Canada. However, ASEAN member countries do not have absolute similarities in the paradigm of counter-terrorism policies. Because ASEAN has the principle of non-interference. Based on these results, it can be concluded that various counter-terrorism policy instruments have been successfully established by ASEAN, which puts forward the perspective of law enforcement. However, there are differences in the paradigm of counter-terrorism by ASEAN member countries.